Phosphorylation of FOXP3 controls regulatory T cell function and is inhibited by TNF-α in rheumatoid arthritis - Nie, Hong; Zheng, Yingxia; Li, Runsheng; Guo, Taylor B; He, Dongyi; Fang, Lei; Liu, Xuebin; Xiao, Lianbo; Chen, Xi; Wan, Bing; Chin, Y Eugene; Zhang, Jingwu Z (Nature medicine, 2013)
TNF-α suppresses regulatory T (T reg ) cell function, however the mechanism remains unclear. Here Jingwu Z Zhang and colleagues find that in activated T cells, phosphorylation of FOXP3 promotes its transcriptional activity. TNF-α induces protein phosphatase 1 expression, leading to dephosphorylation of FOXP3 and inhibition of T reg cell function. In individuals with rheumatoid arthritis, TNF-α–specific antibody treatment restores T reg cell activity and FOXP3 phosphorylation, suggesting that post-translational modifications, including phosphorylation, regulate FOXP3 activity and T reg cell–mediated suppression. Regulatory T (T reg ) cells suppress autoimmune disease, and impaired T reg cell function is associated with rheumatoid arthritis. Here we demonstrate that forkhead box P3 (FOXP3) transcriptional activity and, consequently, T reg cell suppressive function are regulated by phosphorylation at Ser418 in the C-terminal DNA-binding domain. In rheumatoid arthritis–derived T reg cells, the Ser418 site was specifically dephosphorylated by protein phosphatase 1 (PP1), whose expression and enzymatic activity were induced in the inflamed synovium by tumor necrosis factor α (TNF-α), leading to impaired T reg cell function. Moreover, TNF-α–induced T reg cell dysfunction correlated with increased numbers of interleukin-17 (IL-17) + and interferon-γ (IFN-γ) + CD4 + T cells within the inflamed synovium in rheumatoid arthritis. Treatment with a TNF-α–specific antibody restored T reg cell function in subjects with rheumatoid arthritis, which was associated with decreased PP1 expression and increased FOXP3 phosphorylation in T reg cells. Thus, TNF-α controls the balance between T reg cells and pathogenic T H 17 and T H 1 cells in the synovium of individuals with rheumatoid arthritis through FOXP3 dephosphorylation.